Improved of Critical Thinking Skills and Social Skills for Students Through Inquiry Learning (Guided Enquiry) Based Literacy on the Subject of Social Sciences in Class V - Tusriyanto, Tusriyanto; Nadiroh, Nadiroh; Japar, Japar; Wahyudi, Apri; Aminudin, Kodar; Widayati, Eni (Opción, 2019)
Learning social sciences in elementary school should be directed at critical and social thinking skills. Inquiry learning is a series of learning that involves all students ‘ ability to search and investigate systematically, critically, logical- ly and analytically. Given the superficial of material contained in the theme book, so that in this research developed inquiry-based on literacy to expand knowledge and insight. This research aims to explore the improvement of the skills of critical thinking and social skills of students through learning inquiry-based literacy in the courses of social sciences class V Elementary SchoolN 06 Metro Utara. The research design of action research includes de- scribing problems, the assessment of need for a problem, hypotheses of ideas, planning actions (Action Plan), implementation of the plan, evaluating actions and making decisions. Research results show students ‘ critical thinking skills on average (2.84/71%) And the average student social skills (3.04/76%) the criteria is good. As such, researchers recommend learning the literacy-based teaching inquiry to continue to be applied in learning the social sciences class V elementary School as it proved to improve the skills of critical and social skills of students.